Synthesis, X-Ray Crystal Structure Study, Hirshfeld Surface Analysis, and Biological Activity of N-(2-amino-phenyl)-2-methyl-benzamide. (14th November 2016) - Nagaraju, Latha Rani; Venkataravanappa, Lakshmi Ranganatha; Mandayam Anandalwar, Sridhar; Khanum, Shaukath Ara
Abstract : The title compound crystallizes in monoclinic crystal system, with space groupP 2 1 / c . The compound exhibits intermolecular interactions of the types N–H⋯N, C–H⋯O, and C–H⋯ π ; intramolecular interactions of the type N–H⋯N. The intercontacts are also studied using Hirshfeld surface analysis. The compound showed no remarkable antibacterial activity when screened against two gram-negative and two gram-positive bacteria.